A REVIEW ON IMPROVED FINGER PRINT MATCHING USING MINUTIAE SINGULAR POINTS NETWORK. - Prof. Vikas Goyal, Himanshu Jindal (International Journal of Research Science and Management, 2017)
Fingerprint matching is the process used to determine whether two sets of fingerprint ridge detail come from the same finger. There exist multiple algorithms that do fingerprint matching in many different ways. Some methods involve matching minutiae points between the two images, while others look for similarities in the bigger structure of the fingerprint. In this paper, we provide a study of the existing techniques in the area of finger print matching algorithms.